Acute effects and postactivation potentiation in the special judo fitness test - Miarka, B.; Del Vecchio, F. B.; Franchini, E. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to compare the acute short-term effects of (1) plyometric exercise, (2) combined strength and plyometric exercise (contrast), and (3) maximum strength performance in the Special Judo Fitness Test (SJFT). Eight male judo athletes (mean ± SD, age, 19 ± 1 years; body mass, 60.4 ± 5 kg; height, 168.3 ± 5.4 cm) took part in this study. Four different sessions were completed; each session had 1 type of intervention: (a) SJFT control, (b) plyometric exercises + SJFT, (c) maximum strength + SJFT, and (d) contrast + SJFT. The following variables were quantified: throws performed during series A, B, and C; total number of throws; heart rate immediately and 1 minute after the test; and test index. Significant differences were found in the number of throws during series A: the plyometric exercise (6.4 ± 0.5 throws) was superior (p < 0.05) to the control condition (5.6 ± 0.5 throws). Heart rate 1 minute after the SJFT was higher (p < 0.01) during the plyometric exercise (192 ± 8 bpm) than during the contrast exercise (184 ± 9 bpm). The contrast exercise (13.58 ± 0.72) resulted in better index values than the control (14.67 ± 1.30) and plyometric exercises (14.51 ± 0.54). Thus, this study suggests that contrast and plyometric exercises performed before the SJFT can result in improvements in the test index and anaerobic power of judo athletes, respectively.